Anatomical and histological study of the kidneys and salt glands in great flamingos (Phoenicopterus roseus): Ali Faris Reshag, Dhyaa Ab. Abood and Mohammed S. Dawood - Reshag, Ali Faris (The Iraqi Journal of Veterinary Medicine, 2016)
This study was designed to explain the anatomy and histology of kidneys and salt glands in Great Flamingos. Eight adult healthy Great Flamingos of both sexes have been used. The results showed that the kidneys in Great Flamingos consist of three separated lobes. The right kidney was longer 8.9±0.3 mm than the left kidney 8.4±0.4mm. The ratio of the kidneys weight to the total body weight was 0.39%. The salt gland was very large crescent shape, and occupied the supraorbital fossa and has 20.8±0.2mm long and 3.9±0.2mm in diameter. The volume of cortex was 60-70% and the medulla was 30-40%. Within the middle region of cortex there were numerous large corpuscles (mammalian type) and few of small corpuscles (reptilian type). There was a variation between the means diameters of mammalian type 59±1µm and reptilian type 42±0.9µm. The proximal and distal convoluted tubules and collecting ducts were lined by simple cuboidal epithelium and their means diameters were 46±0.9, 44±1 and 55.1±0.7µm, respectively. Within medulla the thick and thin segments were arranged at the peripheral zone of medullary cone while the collecting ducts were at the central part of cone and all were lined with simple cuboidal epithelium except thin segments were lined with squamous cells. The salt gland were consisted of lobules surrounded by thick connective tissue capsule and each has mass of branched tubuloacinar secretory unites. The latter were made up by single layer of cuboidal cells. The tubules lead into central duct lined by double layer of cuboidal cells while the main duct lined with stratified cuboidal epithelium. The secretory units of salt gland gave negative reaction to PAS and combined AB (pH 2.5) and PAS stains and this indicate the absence of neutral mucosubstances. The results concluded that the kidneys in great flamingo was small size organ with low relative weight in compare to birds size and the salt glands was active organ.